THE ROLE OF THE MOSQUE IN ECONOMIC EMPOWERMENTAND COMMUNITY WELFARE - Arif Fauzan; Zainal Arifin Zakaria; Saparuddin Siregar; Armansya Walian (Proceeding International Seminar of Islamic Studies, 2022)
The purpose of this research is to make mosques economically empowered and able to prosper the community. This analytical descriptive research uses a qualitative approach to library research. The results of the study, God's mosques can be independent and prosperous if the baitul maal and the baitul muamalah function and play a good role.Keywords: Empowerment, Prosperity, Baitul Maal, Baitul Muamalah